(untitled) (Pravaha, 2024)
God-gifted talents, best teachers, and best schooling augment the academic performance and students’ motivation is prerequisite for students’ accomplishment. This study attempts to identify the influence of students’ motivation on their academic performance. Three hundred students from various Nepali universities made up the sample. Three-part questionnaires were distributed straight to the intended audience. Personal information is asked in the first few questions; thirty questions from "The University Student Motivation and Satisfaction Questionnaire Version 2," which was used to gauge students’ intrinsic and extrinsic motivation of going to the university. According to the study, students are positively impacted by both intrinsic and extrinsic incentive characteristics. Due to both intrinsic and extrinsic incentive factors they are motivated for giving their effort in study. When comparing variables on an individual basis, students who adjust the self-exploratory, altruistic, and rejection of alternative options variables typically they shows better than those who adjust the career and qualifications, social enjoyment, and social pressure variables. The study emphasizes how important student motivation is to get admitted in the universities.